Ответы и объяснения

Лучший Ответ!
2014-02-27T22:48:38+04:00
=12/(х-2)(х+2)+3/(х+2)=(12+3(х-2))/(х-2)(х+2)=(12+3х-6)/(х-2)(х+2)=(6+3х)/(х-2)(х+2)=3(2+х)/(х-2)(х+2)=3/(х-2)
3/(2002-2)=3/2000=0,0015

х²/(х+1)(х+1)-(х-1)/(х+1)=(х²-(х-1)(х+1))/(х+1)(х+1)=(х²-х²+1)/(х+1)(х+1)=1/(х+1)²
1/(19+1)²=1/20²=1/400=0,0025

(a – b)(a² + ab + b²)/(a² + ab + b²)+(a +b)(a² - ab + b²)/(a² - ab + b²)=(a-b)+(a+b)=2a
2*0,05=0,1

2/(х-2)-12х/(х-2)(х²+2х+4)-(х-2)/(х²+2х+4)=(2(х²+2х+4)-12х-(х-2)(х-2)):(х-2)(х²+2х+4)=(2х²+4х+8-12х-х²+4х-4):(х-2)(х²+2х+4)=(х²-4х+4):(х-2)(х²+2х+4)=(х-2)(х-2):(х-2)(х²+2х+4)=(х-2):(х²+2х+4)
х=0
(-2)/4=-1/2
х=2
(2-2)/(4+4+4)=0/12=0